Social Identity Expressions in Kevin Kwan’s Crazy Rich Asians - Nailul Ifada; Zakiyatul Mufidah (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2019)
The study deals with the expression of social identity in Asians elite community circle found in the novel Crazy Rich Asians by Kevin Kwan. Primary data regarding social identity expressions are noted based on the characters’ utterances and author’s narration found in the novel. The study is categorized as qualitative research as the data are displayed in the form of words from the novel’s original language. The methods of collecting data used by the writer are reading and labeling. The writer acts as the mere observer without other instruments included. Data analysis method includes compiling, disassembling, reassembling, interpreting and concluding based on Robert K. Yin’s techniques of analyzing data. The results indicate that there are a number of social identity expressions in Kwan’s Crazy Rich Asians. There are two significant ways of expressing social identity of the rich: (1) the patterns of consumption including food, fashion, and personal luxury belongings. (2) social image maintenance through early education, interaction, special occasion and club membership.